Serenata a treasury of Kapampangan songs : traditional songs contributed by the common folk of the Kapampangan Region - Lumanug, Edwin (Holy Angel University, Juan D. Nepomuceno Center for Kapampangan Studies, 2009)
"Compilation of lyrics and music notations of over 100 traditional Kapampangan songs collected from all over Pampanga."